Factors influencing attitudes of local communities in the district of Kuching, Sarawak towards the conservation of mangrove forest resources in Kuching mangrove delta - Lee, Sook Yee (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The deltaic mangrove forest areas in the District of Kuching are being destroyed at an alarming rate even though conservation programs are extended to the local communities. This study is carried out to determine the factors that influence the attitudes of the local communities towards conservation of the mangrove forest resources. A total of 326 questionnaires have been collected from 15 villages in the mukim of Sematan, Lundu, Santubong and Matang in the District of Kuching. Data have been collected using face to face interviews of the households in the selected villages. Results from factor analysis show that there are nine factors identified that reflect the attitudes of villagers which include the protection of fauna, payment for conservation, ecotourism, management and conservation programs, economic and commercial values, damage and loss, government responsibility, knowledge and environment. Factors like the socio-demographics, economic activities, location specific of the villages and managerial programs are tested to determine the influence on the attitudes. The results reveal that age, gender, occupation (student), and mangrove replanting have significant causal relationship with attitudes towards conservation. The study shows that the majority of the members of the communities who are living near the mangrove forest in the District of Kuching show positive attitudes toward conservation of mangrove forest resources. Awareness campaign and education of the younger generations should be extended to the local communities to enhance their participation in the conservation of the mangrove forest resources.